Solve the following equation for x

7x-6=-76

1 answer

To solve the equation 7x - 6 = -76 for x, you can follow these steps:

1. Add 6 to both sides: 7x - 6 + 6 = -76 + 6 becomes 7x = -70.
2. Divide both sides by 7: 7x/7 = -70/7 reduces to x = -10.

Therefore, the solution to the equation is x = -10.
Similar Questions
  1. What is the first step in solving the linear system{2x − 3y = 11 {−x + 5y = −9 by the substitution method in the most
    1. answers icon 2 answers
  2. What is the first step in solving the linear system{2x−3y=11 {−x+5y=−9 by the substitution method in the most efficient
    1. answers icon 4 answers
  3. Solving Multi-Step Equation Quiz1.Solve the Equation x5=−2 A. -35 B. -10 C.3 2. Solve the equation. x5+1=−7 A. -13 B. -40 C.
    1. answers icon 1 answer
  4. You need to solve this equation for x: ax-7=26Which equation would be best first step you could make to solve the equation? (1
    1. answers icon 1 answer
more similar questions